Virtual Tour Design Through Google Street 360° at Pariaman Tourism Object as A Travelling Alternative During Covid Pandemic Outbreak - Rafidola Mareta Riesa; Alhapen Ruslin Chandra; Erica Aneysa (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2022)
This study aims to produce a virtual video tour of tourist attractions in Pariaman City via Google Street 360°. The research method used in this study is a qualitative approach with a design method that uses data collection techniques obtained from several journals published on the internet and also uses several library sources from electronic media. Based on research using Multimedia Development Life Cycle (MDLC) as a design method, a product is produced in the form of a video One-day virtual tour of Kota Pariaman using several stages. The first stage is determining the concept, the second stage is determining the design, the third stage is the collection of materials, the fourth stage is assembly, the fifth stage is testing and the sixth stage is distribution.